2019
DOI: 10.3389/fonc.2019.00603
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors Available for Chronic Myeloid Leukemia: Efficacy and Safety

Abstract: Chronic myeloid leukemia (CML) is currently a disease in which patients can enjoy a near normal life-expectancy. However, since the majority of patients will need to remain on treatment indefinitely, physicians in care of CML patients need be familiar with the indications and toxicities of all approved tyrosine kinase inhibitors (TKI). In clinical practice, there are five TKI (imatinib, nilotinib, dasatinib, bosutinib, and ponatinib) that are available in different scenarios and have distinct safety profiles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 84 publications
1
89
0
3
Order By: Relevance
“…For instance, the results of the ENESTnd prospective randomized study showed that the incidence of cardiovascular events after 6 years was 10% in patients treated with nilotinib (5% ischemic heart disease, 1.4% ischemic cerebrovascular disease, and 4.3% peripheral arterial disease) as compared to 2.5% in imatinib-treated patients [20]. Consequently, current experts' recommendations advocate against the use of nilotinib in patients with a high-risk cardiovascular profile, whenever possible [21].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the results of the ENESTnd prospective randomized study showed that the incidence of cardiovascular events after 6 years was 10% in patients treated with nilotinib (5% ischemic heart disease, 1.4% ischemic cerebrovascular disease, and 4.3% peripheral arterial disease) as compared to 2.5% in imatinib-treated patients [20]. Consequently, current experts' recommendations advocate against the use of nilotinib in patients with a high-risk cardiovascular profile, whenever possible [21].…”
Section: Discussionmentioning
confidence: 99%
“…These receptors have specific growth factors as ligands and are involved in several fundamental functions for cell survival and activation, such as growth, differentiation, and apoptosis [13][14][15][16]. The oncogenic role of their alterations is well documented, as well as their possible exploitation as therapeutic targets [17][18][19][20][21][22][23][24][25].…”
Section: Characteristics Of Ntrk Genes and Of Trk Signalingmentioning
confidence: 99%
“…The development of a BCR/ABL kinase inhibitor, imatinib, was a significant major improvement in CML treatment [24]. However, imatinib, and second and third-generation tyrosine kinase inhibitors' effectiveness is often inadequate as resistant CML stem cells and residual disease persist in many patients [25][26][27]. Genomic sequencing of CML patients has identified additional genetic changes, like mutations of the tumor suppressor genes RB1, TP53, and CDKN2A [28], and highlighted the fact that BCR-ABL kinase mutations are only identified in approximately 50% of patients with poor responses and disease progression [29].…”
Section: Chronic Myeloid Leukemia (Cml)mentioning
confidence: 99%